High-purity capture and release of circulating exosomes using an exosome-specific dual-patterned immunofiltration (ExoDIF) device. Issue 36 (1st September 2017) - Kang, Yoon-Tae; Kim, Young Jun; Bu, Jiyoon; Cho, Young-Ho; Han, Sae-Won; Moon, Byung-In
Abstract : We present a microfluidic device for the capture and release of circulating exosomes from human blood. Abstract : We present a microfluidic device for the capture and release of circulating exosomes from human blood. The exosome-specific dual-patterned immunofiltration (ExoDIF) device is composed of two distinct immuno-patterned layers, and is capable of enhancing the chance of binding between the antibody and exosomes by generating mechanical whirling, thus achieving high-throughput exosome isolation with high specificity. Moreover, follow-up recovery after the immuno-affinity based isolation, via cleavage of a linker, enables further downstream analysis. We verified the performance of the present device using MCF-7 secreted exosomes and found that both the concentration and proportion of exosome-sized vesicles were higher than in the samples obtained from the conventional exosome isolation kit. We then isolated exosomes from the human blood samples with our device to compare the exosome level between cancer patients and healthy donors. Cancer patients show a significantly higher exosome level with higher selectivity when validating the exosome-sized vesicles using both electron microscopy and nanoparticle tracking analysis. The captured exosomes from cancer patients also express abundant cancer-associated antigens, the epithelial cell adhesion molecule (EpCAM) on their surface. Our simple and rapid exosome recovery technique has huge potential to elucidate the function of exosomes in cancer patients and can thus be applied for various exosome-based cancer research studies.